Investigation of Nerve Fiber Network in THz Spectrum Range - Hovhannisyan, T.; Makaryan, A.
The behavior of the nerve fiber system of the spinal cord of animals in the THz wavelength range (0.1-3 THz) was experimentally studied using a time domain spectrometer. Terahertz wave transmittance of nerve tissue is investigated, when DC voltage is applied to the sample. It has been shown that when a constant voltage is applied along the nerve fibers (also in the absence of voltage), no noticeable changes occur in the transmitted THz wave, regardless of the orientation of the sample relative to the THz E-field vector. Significant changes in the electrodynamic properties of the sample were observed when the nerve fibers were parallel to the THz E-field vector and the applied voltage was perpendicular to the nerve fibers, particularly, resonant absorption was observed at frequencies of 0.6 THz and 2 THz.
Keywords: Physics